(untitled) (Philosophy and Progress, 2023)
The paper explores the logical structure of Rawlsian justice principles in order to see whether their justificatory or explanatory conditions are unproblematic. To facilitate this purpose, drawing on readers of Rawls, the author shows that the Aristotelian principle is used to explain the principles of rational choice, particularly the principle of inclusiveness. Then, on the basis of the Aristotelian principle, Rawls justifies his conclusion, via the principles of rational choice and the theory of primary goods. After figuring out the logical structure of justice as fairness, the author deals with the central objective of the paper, where he exposes some problems suffered by the motivational basis of the principles of justice. The foundation on which Rawls grounds his principles of justice is problematic, and consequently, they remain as matters of contention as of today. Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 45-60